(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2010)
Makalah ini membincangkan kefungsian gaya bahasa pengulangan dalam novel Al-Abrar yang dianalisis menggunakan pendekatan wacana. Tujuan analisis dibuat adalah untuk melihat kefungsian gaya bahasa pengulangan yang ditinjau penggunaannya dalam aras perenggan. Teori Halliday (1985) yang memanfaatkan tema dan rema akan diaplikasikan bagi menjelaskan kefungsian gaya bahasa pengulangan tersebut. Terdapat lapan gaya bahasa pengulangan yang dikenal pasti iaitu pengulangan anafora, simplok, anadiplosis dan paralelisme yang berfungsi sebagai unsur penjelasan, pengembangan, pengharmonian dan penambahan idea dalam perenggan. Pengulangan epizeuksis dan mesodiplosis berfungsi sebagai unsur penegasan dan sokongan hujah. Manakala pengulangan epistrofa dan epanalepsis berfungsi sebagai unsur pelengkap fakta dan penegasan maksud dalam perenggan. This article discusses the functionality of repetition in the Al-Abrar novel based on a discourse approach. The purpose of this analysis is to investigate the functionality of repetition at the paragraph level. Halliday’s theory (1985) which uses themes and rhemes was used to explain the functionality of repetition in the novel. Eight forms of repetition were identified. Four of them are anaphora, symploke, anadiplosis and parallelism which function as idea explanation, idea expansion, idea harmonization and idea addition respectively. The rest are epizeuxis and mesodiplosis which function as argument emphasis and support, as well as epistrophe and epanalepsis which function as fact complements and meaning-emphasis in a paragraph.